Modified Mineral Trioxide Aggregate—A Versatile Dental Material: An Insight on Applications and Newer Advancements - Pushpalatha, C.; Dhareshwar, Vismaya; Sowmya, S. V.; Augustine, Dominic; Vinothkumar, Thilla Sekar; Renugalakshmi, Apathsakayan; Shaiban, Amal; Kakti, Ateet; Bhandi, Shilpa H.; Dubey, Alok; Rai, Amulya V.; Patil, Shankargouda (Frontiers in Bioengineering and Biotechnology, 2022)
Mineral Trioxide Aggregate (MTA) has been a material of revolution in the field of dentistry since its introduction in the 1990s. It is being extensively used for perforation repairs, apexification, root-end filling, obturation, tooth fracture repair, regenerative procedures, apexogenesis, pulpotomies, and as a pulp-capping material because of its desired features such as biocompatibility, bioactivity, hydrophilicity, sealing ability, and low solubility. Even though its application is wide, it has its own drawbacks that prevent it from reaching its full potential as a comprehensive replacement material, including a long setting time, discoloration, mud-like consistency, and poor handling characteristics. MTA is a material of research interest currently, and many ongoing studies are still in process. In this review, the newer advancements of this versatile material by modification of its physical, chemical, and biological properties, such as change in its setting time, addressing the discoloration issue, inclusion of antimicrobial property, improved strength, regenerative ability, and biocompatibility will be discussed. Hence, it is important to have knowledge of the traditional and newer advancements of MTA to fulfill the shortcomings associated with the material.